A Computational Analysis of the Energy Harvested by Gfrp and Nfrp Laminated Beams Under Cyclic Loading. (2017) - Fragoudakis, Roselita; Gallagher, John A.; Kim, Vladimir
Abstract: This paper investigates the possibility of energy harvesting using Fiber Reinforced Plastic beams under cyclic loading. The behaviour of E-glass fiber/epoxy and Hemp fiber/epoxy laminated beams reinforced with piezoelectric fibers is examined by evaluating their bending strain and deflection. An optimum stacking sequence for all types of reinforcement: E-glass fibers, hemp fibers, and piezoelectric fibers, is suggested such that energy harvesting potential is maximized while failure and damage accumulation remain at low levels.